Successful retrieval of a retained J guidewire from the right atrium and aorta arch using a self-invented snare device - Chen, Chuan; Bhattarai, Robin; Yang, Yang; Ling, Cong; Luo, Lun; Wang, Hui (Nepal Journal of Neuroscience, 2021)
Guidewire retention during an interventional treatment is a very rare complication that can lead to possible serious complications, such as thrombosis, embolization, sepsis, and perforation. Hence, a retained guidewire must be retrieved as soon as possible. Here, we provide the first report of a case of accidental retention of a 0.035” J guidewire in the right atrium and aortic arch during basilar artery aneurysm embolization. We found that due to the heavier weight of the J guidewire and its hydrophilic-coated layer, it could not be removed using previously reported methods for micro-guidewire retention. Therefore, we constructed a self-invented snare device consisting of a 0.014” micro-guidewire and a 4-Fr MP-A1 catheter and successfully retrieved the J guidewire, thus avoiding open surgery and its associated serious complications. According to our experience, this novel technique described here is quite easy to perform, safe and effective and can avoid serious complications and prevent the need for open surgery.